The effect of hypnosis on the reduction of mental and physical diseases - Zahra Sotoudeh; Maryam Ghorbani (روانشناسی و روانپزشکی شناخت, 2019)
Introduction: According to human studies, mental and psychological problems have an irreversible impact on the human. Today, Hypnosis is one of the treatments in many areas of medical science and psychotherapy. Specialists in this field used this treatment to improve patient`s therapy. Aim: the purpose of this study was to investigate the effect of hypnotherapy on the reduction of psychological and physical problems. Method: This is review article and survey some past studies conducted on the effects of hypnotherapy on the reduction of psychological and psychological problems. Results: finding showed that is usefull in reducing the patient`s problem. Conclusion: The results have shown that hypnosis has the potential to be effective in reducing various problems in various physical and mental disorder. Therefore, hypnosis can be considered as one of the effective therapies for disorders.